Research on Fluid Transient and Operation Scheduling Safety of Water Supply System - YUAN Zhe; ZHOU Zixuan (Renmin Zhujiang)
In order to prevent the water hammer caused by the change of water demand and accidental pump stop in the actual operation of the water supply system,based on the actual water supply project and method of characteristics,this paper establishes the hydraulic transition process model of the pump water supply system,and studies the fluid transient review and the optimization of operation scheduling safety.The actual project shows that without water hammer protection measures,the excessive negative pressure will occur in the pipeline in case of accidental pump stop.By taking the water hammer protection measures on the surge tower at lower positions,the negative pressure is effectively avoided and the safe operation of water supply system is guaranteed.By reducing the water supply pressure at the access point of the water plant,while ensuring the system safety,the water supply of the pump set is increased,the energy saving benefits are improved,and the economic operation of water supply projects is realized.